Associations of social networks with quality of life, health and physical functioning. (2nd April 2016) - Bergland, Astrid; Meaas, Ingrid; Debesay, Jonas; Brovold, Therese; Jacobsen, Ellisiv Lærum; Antypas, Konstantinos; Bye, Asta
Abstract: The aim of this study was to assess whether demographic and social network variables, independently of each other, are associated with quality of life (QoL), self-rated health or physical function. The sample consisted of 307 women aged ≥ 75 years. Social networks were assessed by Fillenbaum's five questions and a question on ability to participate in organizations. Variables of demographic composition, QoL, health and physical function were registered. We found significant associations between social networks, QoL, health and physical functioning. Seeing friends and relatives as often as wanted, getting help when sick or disabled and having no problems participating in organizations were associated with higher QoL. Higher educational level, the ability to see friends and relatives as often as wanted and having no problems participating in organizations were associated with better health. Living alone, getting help when sick or disabled and having no problems participating in organizations indicated better mobility. Being younger, having higher education and no problems in participating in organizations were associated with better balance. Higher scores on muscle strength were associated with being younger, not living alone and having no problems in participating in organizations. Our results highlight the importance of social networks for maintaining good QoL, health and physical functioning.